2013
DOI: 10.3390/ijms140919230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gln223Agr Polymorphism of Leptin Receptor Gene in Type II Diabetic Mellitus Subjects among Malaysians

Abstract: Leptin is known as the adipose peptide hormone. It plays an important role in the regulation of body fat and inhibits food intake by its action. Moreover, it is believed that leptin level deductions might be the cause of obesity and may play an important role in the development of Type 2 Diabetes Mellitus (T2DM), as well as in cardiovascular diseases (CVD). The Leptin Receptor (LEPR) gene and its polymorphisms have not been extensively studied in relation to the T2DM and its complications in various population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…There was no obvious association between LEPR Gln223Arg polymorphism and T2DM in Asians either (G vs. A, OR = 1.08, 95% CI 0.75 to 1.57, P = 0.68) (Fig. 3) [5][6][7][8][10][11][12][13]15]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no obvious association between LEPR Gln223Arg polymorphism and T2DM in Asians either (G vs. A, OR = 1.08, 95% CI 0.75 to 1.57, P = 0.68) (Fig. 3) [5][6][7][8][10][11][12][13]15]. …”
Section: Resultsmentioning
confidence: 99%
“…1), we excluded seven studies which were not according to HWE, and the I 2 was reduced to 47.9% (Fig. 2) [6,7,9,10,14,15]. Sixteen individual studies with 7827 subjects were finally included into the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEPR rs1137101 polymorphism (Q223R; Gln223Arg; 668A > G) is an A> G substitution resulting in the exchange of glutamine for arginine at position 668 of LEPR (Figure 1). The presence of this variant was considered as an independent risk factor for T2DM in Malaysian subjects (48). Finns with glucose intolerance and the presence of the GG genotype (Finnish Diabetes Prevention Study) showed a higher risk for T2DM compared to those carrying the A allele.…”
Section: Lepr Rs1137100 and Rs1137101 Polymorphismsmentioning
confidence: 99%
“…The International Diabetes Federation (IDF) has predicted that the number of people with diabetes will rise from 285 million in 2010 to 439 million in 2030. In Malaysia, the proportion of known diabetes is estimated to have increased from 6.5 to 9.5%, accompanied by a three-fold enlargement in newly diagnosed cases from 1.8 to 5.4% over the same period (Letchuman et al, 2010;Etemad et al, 2013;Haghvirdizadeh, et al, 2015). Malaysia has different subethnic groups (Hatin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%